2009
DOI: 10.1093/treephys/tpp050
|View full text |Cite
|
Sign up to set email alerts
|

Pinus taeda clones and soil nutrient availability: effects of soil organic matter incorporation and fertilization on biomass partitioning and leaf physiology

Abstract: The combined effects of intensive management and planting of improved seedlings have led to large increases in productivity on intensively managed pine forests in the southeastern United States. To best match clones to particular site conditions, an understanding of how specific clones respond to changes in nutrition in terms of biomass partitioning, leaf physiology and biochemistry will be necessary. This study measured the response of biomass partitioning, light-saturated net photosynthesis (A(Sat)) and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Fertilizer was applied two times over the course of the experiment. Application rates were selected to maintain consistency with a complimentary field experiment (Tyree et al, 2009a). The first application was on July 28, 2006 in the form of diammonium phosphate (DAP) and ammonium nitrate (AN) at an equivalent rate of 200 kg N and 50 kg P ha À1 .…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizer was applied two times over the course of the experiment. Application rates were selected to maintain consistency with a complimentary field experiment (Tyree et al, 2009a). The first application was on July 28, 2006 in the form of diammonium phosphate (DAP) and ammonium nitrate (AN) at an equivalent rate of 200 kg N and 50 kg P ha À1 .…”
Section: Treatmentsmentioning
confidence: 99%
“…ha À1 ), had little effect on overall tree growth (Tyree et al, 2009b). Another study found that contrasting Pinus taeda clones grown in the field responded differently to LR incorporation with one clone being negatively affected while the other clone showed no effect (Tyree et al, 2009a). In addition to possible effects on plant productivity, the incorporation of LR into the mineral soil would likely accelerate decomposition rates possibly negating any possible increases to soil C (LundmarkThelin and Johansson, 1997;Ouro et al, 2001;Perez-Batallon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In order to maximize growth potential in clonal plantations to justify more expensive genetic material at planting, fertilization and other intensive silvicultural practices will need to be applied (Dougherty 2007). However, differences in morphology and development among clones may require different silvicultural prescriptions for different clones (Roth et al 2007;Tyree et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, variable growth responses to fertilizer application have been observed among a small number of clones (King et al, 2008;Espinoza, 2009;Tyree et al, 2009b). However, we are aware of no information currently available in the literature on clonal fertilizer growth response involving more than eight clones of P. taeda.…”
Section: Introductionmentioning
confidence: 99%